A Review on Christian Political Theology in the Twentieth Century - AN, Ximeng (Journal of Research for Christianity in China (JRCC), 2025)
This article belongs to a fragment of the development history of Christian theological thought. Political theology goes back to the Stoics. Schmitt revived political theology in the 20th century. Political theology remains the current of thought in Europe. European society has been reinvented by various waves of criticism. The themes of political theology were revived in the 1960s. The emphasis on the political sphere is once again having an impact. Modern political theology puts forward a new view on the relationship between theology and politics. Political theology is not the same as forcing theologians and pastors to "talk politics". Modern political theology pays more attention to this side than to the reverie of the world beyond. More concrete than abstract. More public than private. Practice is more than speculation. History is more concrete than metaphysics. There is more contemplation of suffering than of heaven. The former political theology identifies with the status quo, while the new political theology is critical, practical, revolutionary, rebellious, liberating, radical and public.Political theology accepts the critical, revolutionary, practical and public nature of Marxism.They take Marx's criticism of religion seriously. It also criticizes church institutions and theological traditions. "Depersonalization" is also the creed of all political theologians. Moltmann emphasized the differentiation between old and new political theology. The old outdated political theology is called political religion. The "submission" of religion to the secular society is the political religion that takes religion as its handmaid. On the other hand, European political theology also lacks the practical social steps of the gun-toting priests of liberation theology.
Keywords: Political theology, Christianity, Marxism, Moltmann